Ultrasensitive allele inference from immune repertoire sequencing data with MiXCR - Mikelov, Artem; Nefediev, George; Tashkeev, Alexander; Rodriguez, Oscar L; Aguilar Ortmans, Diego; Skatova, Valeriia; Izraelson, Mark; Davydov, Alexey N; Poslavsky, Stanislav; Rahmouni, Souad; Watson, Corey T; Chudakov, Dmitriy; et al. (Genome research, 2024)
Allelic variability in the adaptive immune receptor loci, which harbor the gene segments that encode B cell and T cell receptors (BCR/TCR), is of critical importance for immune responses to pathogens and vaccines. Adaptive immune receptor repertoire sequencing (AIRR-seq) has become widespread in immunology research making it the most readily available source of information about allelic diversity in immunoglobulin (IG) and T cell receptor (TR) loci. Here, we present a novel algorithm for extrasensitive and specific variable (V) and joining (J) gene allele inference, allowing the reconstruction of individual high-quality gene segment libraries. The approach can be applied for inferring allelic variants from peripheral blood lymphocyte BCR and TCR repertoire sequencing data, including hypermutated isotype-switched BCR sequences, thus allowing high-throughput novel allele discovery from a wide variety of existing data sets. The developed algorithm is a part of the MiXCR software. We demonstrate the accuracy of this approach using AIRR-seq paired with long-read genomic sequencing data, comparing it to a widely used algorithm, TIgGER. We applied the algorithm to a large set of IG heavy chain (IGH) AIRR-seq data from 450 donors of ancestrally diverse population groups, and to the largest reported full-length TCR alpha and beta chain (TRA and TRB) AIRR-seq data set, representing 134 individuals. This allowed us to assess the genetic diversity within the IGH, TRA, and TRB loci in different populations and to establish a database of alleles of V and J genes inferred from AIRR-seq data and their population frequencies with free public access through VDJ.online database.
Keywords: Genetic Variation; vysoce účinné nukleotidové sekvenování; alely; sekvenční analýza DNA; Receptors, Antigen, T-Cell; Sequence Analysis, DNA; receptory antigenů T-buněk; algoritmy; Receptors, Antigen, B-Cell; genetická variace; software; Humans; Alleles; Algorithms; High-Throughput Nucleotide Sequencing; Software; receptory antigenů B-buněk; lidé